Local versus landscape effects of bush encroachment on plant available light, soil moisture, frost occurrence and herbaceous productivity and composition - Klopper, Chrisna (Rhodes University, Faculty of Science, Botany Department, 2016)
Bush encroachment is a global phenomenon and a pressing concern for South Africa rangelands. The expansion and increase in density of Vachellia karroo (hereafter referred to aAcacia karroo) has been documented in the Eastern Cape and KwaZulu Natal in South Africa. This increase in woody species in savannas is often at the expense of grass cover and thus is causing concern about how this will impact agriculture due to possible loss of grazing capacity. To understand the impacts of bush encroachment the effect of trees on their micro-climate and abiotic factors and in turn on the herbaceous layer needs to be examined. The objective of this study was to quantify the effect of Acacia karroo encroachment on the light environment, soil moisture and frost occurrence in the sub-canopy and inter-canopy micro-habitats, and how these changes affected herbaceous player productivity and composition. Another question that is being addressed here is whether, and how, the local tree effects scale up in the landscape and whether prediction can be made based on the effects of individual trees. The study was undertaken on a farm, Endwell, in the Smaldeel, Eastern Cape. At the study site, a semi-arid savanna, Acacia karroo has been encroaching since the 1980's. The study was conducted at three scales: landscape, stand-wide and local scale. The landscape scale was represented by four areas with 0, 21, 45 and 72% tree canopy cover, the stand-wide scale consisted of transects with varying percentages of tree canopy cover within each of the four levels of encroachment. The local scale was represented by the sub-canopy and inter-canopy environment to test the effect of trees. At the local scale plant available light and soil moisture were lower in the sub-canopy than intercanopy regions, with leaf area index being higher in the sub-canopy. This local negative effect of the tree canopy on light and soil moisture in the sub-canopy did not scale up predictably in the landscape. At the stand-wide scale light in the inter-canopy was reduced as shading increased. Frost was excluded from under the canopies and frost incidence decreased at higher tree cover. Grass productivity was reduced in the sub-canopy, possibly due to lower light and soil moisture. Overall biomass increased from the low to medium level of encroachment but lowest at the high level of encroachment. Grass composition and cover was only slightly affected by tree canopies cover and C4 grass species were still present in the sub-canopy and at lower light environments. At the levels of Acacia karroo encroachment encountered at this study site, it seems unlikely that palatable or desirable C4 would be excluded from the system and that a shift from C4 to shade-tolerant species would occur. This is due to tree canopies at the site not reducing light to such anextent that they would outcompete grasses, and likely the very low grazing pressure at thesesites. Herbaceous biomass at these sites were still sufficient to carry a fire in the inter-canopyregion and sufficient grazing for herbivores. In the sub-canopy region fires will be excluded thus with higher the portion of sub-canopy areas increasing at the high levels of encroachment they may interrupt fire spread. Thus it was concluded that Acacia karroo encroachment up to 45% tree cover is currently not creating negative feedback on herbivory, but low stocking rates appear to be key to maintain this.
Keywords: Uncatalogued